THE POTENTIAL OF DIGITAL LEARNING PATHS FOR PROVIDING EQUITABLE CONDITIONS FOR LEARNING ENGLISH GRAMMAR - Busack, Eirini (Proceedings of the International Conference on Education, 2023)
The purpose of this article is to present a case study that explores the effectiveness of digital learning paths (DLPs) in improving English grammar proficiency among English language learners in secondary schools (Years 6-10), and to assess their potential for promoting equity in classroom instruction. To answer this question, we provided the English teachers with access to our grammar-focused DLPs, which were relevant to the year they were teaching, so that they can plan a 45-minute English grammar lesson that combines the book and the DLP, be it theory and/or context and/or exercises. Learners were given access to the DLP via tablets. The data about pupils’ reactions was collected via lesson observation and an online questionnaire, made up of 16 multiple-choice closed questions that pupils filled in immediately after the DLP-supported English grammar lesson. Our results showed that pupils felt supported in the following four areas during the DLP-supported lesson: 1. Technology-enhanced learning; 2. Stimulating teaching and learning materials; 3. Open access to additional learning materials (theory and exercises); 4. Freedom to choose the exercises according to the individual’s level of knowledge. This study takes place as part of the BMBF-project InDiKo that research media-didactic competence development in pre-service teachers; the English team works on the development, implementation, and evaluation of narrative Innovation Space-based DLPs on grammar, created by the pre-service English teachers in a media-didactics/Grammar double-seminar at the University of Education Karlsruhe. By attempting to address multiple factors and learner characteristics simultaneously, DLPs can be seen as facilitating the learning process by promoting learner-centred and differentiated learning.